Study of the influence of protuberances in the trailing edge of airfoils and determination of their aerodynamic efficiency through CFD using Ansys Fluent ... : Estudio de la influencia de protuberancias en el borde de ataque de perfiles alares y determinación de su eficiencia aerodinámica mediante CFD en Ansys Fluent ... - González, Angel; Hinojosa, Jorge (Barcelona : Scipedia, 2019)
In the present research, the effect of incorporating protuberances in the leading edge to the aerofoil NACA-0012 was studied. For the simulations, two profiles were designed: parametric profile (NACA 0012) and modified profile (0012-MOD), with help of CAD Program Inventor Professional 2016. The 0012-MOD profile incorporates modifications in the leading edge, whose inspiration comes from malformations present on the flippers of the humpback whale (Megaptera novaeangliae). The computational simulations were performed in Ansys Fluent, using the turbulent viscosity model k-ε realizable, with SIMPLE calculation algorithm. The study fluid is air in the incompressible range with Ma: 0.11. To obtain the lift and drag curves for both profiles, they were simulated for angles of attack α: between 0° and 40°, this way it will be possible to compare the profiles and determine their aerodynamic behaviour. ... : En la presente investigación se estudió el efecto de incorporar protuberancias en el borde de ataque al perfil aerodinámico NACA-0012. Para las simulaciones se diseñaron dos perfiles: perfil paramétrico (NACA 0012) y perfil modificado (0012-MOD), con ayuda del programa CAD Inventor Professional 2016. El perfil 0012-MOD incorpora modificaciones en el borde de ataque, cuya inspiración proviene de las malformaciones presentes en las aletas de la ballena jorobada (Megaptera novaeangliae). Las simulaciones computacionales se realizaron con el software comercial Ansys Fluent®, utilizando el modelo de viscosidad turbulenta k-ε realizable, con algoritmo de cálculo SIMPLE. El fluido de estudio es aire en el rango incompresible con Ma: 0,29. Con el objeto de obtener las curvas de sustentación y arrastre para ambos perfiles, se realizaron simulaciones para ángulos de ataque α entre los 0° y los 40°, de esta forma será posible comparar los perfiles y determinar su comportamiento aerodinámico. ...